Cover Image, Volume 40, Issue 5. Issue 5 (16th April 2019) - Li, Xiaojin; Zhang, Wei; Zhou, Donghu; Lv, Tingxia; Xu, Anjian; Wang, Hejing; Zhao, Xinyan; Zhang, Bei; Li, Yanmeng; Jia, Siyu; Wang, Yu; Wang, Xiaoming; et al.
Abstract : On the cover : This cover image is an artistic representation of the Research Article Complex ATP7B mutation patterns in Wilson disease and evaluation of a yeast model for functional analysis of variants by Xiaojin Li et al., DOI:10.1002/humu.23761 . Illustration Credit: Mrs. Shijia Tang.